Hepatic nuclear factor kappa B regulates neutrophil recruitment to the injured brain. - Campbell, S; Anthony, D; Oakley, F; Carlsen, H; Elsharkawy, A; Blomhoff, R; Mann, D (2008)
Acute brain injury is associated with induction of hepatic chemokine expression, which is an essential element in the subsequent recruitment of leukocytes to the damaged brain. To further understand the significance of the hepatic inflammatory response, we focused on nuclear factor (NF)-kappa B, a pivotal regulator of inflammation. Nondestructive real-time whole-body imaging was undertaken in the 3XNF-kappa B-luciferase mouse to monitor NF-kappa B activation. Acute brain injury induced by intracerebral injection of interleukin-1 provoked rapid activation of hepatic and CNS NF-kappa B, with only minimal changes in other organs. Elevated NF-kappa B in the brain was limited to the site of the lesion, whereas hepatic NF-kappa B was widespread. The function of NF-kappa B in this model was determined by monitoring leukocyte recruitment to the liver and brain of nf kappa b1 mice, which lack the anti-inflammatory p50:p50 NF-kappa B homodimer. Brain injury in the nf kappa b1 mice was associated with increased neutrophil recruitment to the liver and brain compared with wild-type mice, thereby confirming a regulatory role for the NF-kappa B system. To determine the role of hepatic NF-kappa B, it was selectively inhibited by intravenous adenoviral-mediated delivery of an I kappa B alpha super-repressor. This treatment significantly reduced the numbers of neutrophils recruited to the brain. In conclusion, acute brain injury is associated with rapid and robust activation of hepatic NF-kappa B, which is required for efficient mobilization of circulating leukocytes to the brain.